Upper Paleocene paleoenvironmental reconstruction using Coccolithus pelagicus and δ¹³C stratigraphy from the Al-Uwayliah Formation, northeastern Libya.1 - S. Hassan , Hassan (Libyan Journal of Science &Technology, 2026)
Marine chalk rocks in the north-east of Libya are an archive of sea conditions that evolved after the boundary between the Cretaceous and Paleogene periods in the southern part of Tethys. In the Al-Uwayliyah Formation of the Jabal Akhdar region, Coccolithus pelagicus, which reflects paleoenvironmental conditions, is found within the upper Paleocene chalky limestones. In a re markably well preserved stratigraphic sequence, primarily Paleocene rocks are found, providing good opportunities for late Paleocene marine environments to be precisely reconstructed. Paleoenvironmental interpretation integrates four data sources: mineral composition, micro scopic texture, nannofossil assemblages, and carbon isotope (δ¹³C) ratios. Before the Paleocene Eocene Thermal Maximum, conditions in surface waters and carbon cycling were assessed using this data. The main composition of the dominant chalk-wackestone facies is of pelagic carbonate ooze, rich in planktonic foraminifers and nannoplankton. From mid to outer shelf depths, sedi ments built up in quiet, wide areas of the seafloor - no strong currents involved. Because rivers did not reach far out, land-derived particles stayed scarce here. Calm conditions meant organ isms mixed nutrients efficiently, leaving behind minimal biological waste. Freshwater runoff brought some silt now and then yet overall supply stayed low. Over time, gentle flows delivered tiny particles that settled slowly beneath the surface layer. Out at the edge of the Paleogene, surface waters likely stayed chilly thanks to a swarm dominated by Coccolithus pelagicus. Nutrients seemed decent, circulation smooth, temperatures within range for cool zones. Near the close of the Paleocene, a slight bump in carbon isotope values appeared - then softened until just before the Eocene takeover. That rise, then fade, lines up well with earlier carbon trends during the PETM era, though one big detail is missing: any dip in iso topic signal.